2023
DOI: 10.1007/s10597-022-01076-9
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health, Substance Use, Physical Health, and Mental Health Treatment Need of Community Individuals Experiencing Homelessness in Hawai‘i

Abstract: Limited research has examined the mental health of individuals experiencing homelessness in Hawai'i, which bears the nation's second highest homelessness rate. Mental health, substance use, treatment need, and health data were collected from 162 unhoused individuals in Hawai'i County by visiting community locations where they congregate (e.g., beaches, vacant buildings). 77% of participants were Native Hawaiian/Pacific Islander (NH/PI) with participants demonstrating severe rates of mental and substance use di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In adults, 2019 NSDUH data revealed low rates of AA-NH/PI past-year use of 1.7% for opioids and > 1% for methamphetamines [88] with a community study of NH/PI adults also finding low rates of current opioid and methamphetamine use of 1% for both substances [29]. Yet, a followup study targeting Hawai′i unhoused individuals-driven by community reports of high NH/PI use in this population-found that over 75% of participants were NH/PI and that this population experienced severe rates of current (1) methamphetamine and illicit opioid use (69% and 24%) and (2) methamphetamine use disorders and OUDs (74% and 12%) [97], revealing key pockets of NH/PIs at great overdose risk who are typically overlooked in national and community studies/data.…”
Section: Illicit Substance Usementioning
confidence: 97%
“…In adults, 2019 NSDUH data revealed low rates of AA-NH/PI past-year use of 1.7% for opioids and > 1% for methamphetamines [88] with a community study of NH/PI adults also finding low rates of current opioid and methamphetamine use of 1% for both substances [29]. Yet, a followup study targeting Hawai′i unhoused individuals-driven by community reports of high NH/PI use in this population-found that over 75% of participants were NH/PI and that this population experienced severe rates of current (1) methamphetamine and illicit opioid use (69% and 24%) and (2) methamphetamine use disorders and OUDs (74% and 12%) [97], revealing key pockets of NH/PIs at great overdose risk who are typically overlooked in national and community studies/data.…”
Section: Illicit Substance Usementioning
confidence: 97%